2002
DOI: 10.1093/jee/95.5.1018
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Resistance to Bt Toxin Cry1Ac in a Field-Derived Strain of Pink Bollworm (Lepidoptera: Gelechiidae)

Abstract: Laboratory selection with Cry1Ac, the Bacillus thuringiensis (Bt) toxin in transgenic cotton, initially produced 300-fold resistance in a field-derived strain of pink bollworm, Pectinophora gossypiella (Saunders), a major cotton pest. After additional selection increased resistance to 3,100-fold, we tested the offspring of various crosses to determine the mode of inheritance of resistance to Cry1Ac. The progeny of reciprocal F1 crosses (resistant male x susceptible female and vice versa) responded alike in bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
100
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 0 publications
4
100
2
2
Order By: Relevance
“…Dominance of resistance in other selected populations against Cry toxins has revealed both recessive and incompletely dominant resistance that can vary depending on the concentration of the toxin used. However, the general pattern frequently found shows that the degree of dominance decreases with increasing toxin concentration (34,44,45), the opposite trend to that found in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Dominance of resistance in other selected populations against Cry toxins has revealed both recessive and incompletely dominant resistance that can vary depending on the concentration of the toxin used. However, the general pattern frequently found shows that the degree of dominance decreases with increasing toxin concentration (34,44,45), the opposite trend to that found in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The degree of dominance (h) was estimated using the single-concentration method, based on Hartl's definition of dominance and on survival at any single concentration (44).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent molecular work with the NO-QA strain mapped genetic control of its Cry1A resistance to a single chromosomal location (Heckel et al 1999). With pink bollworm resistance to Cry1Ac in the AZP-R strain from Arizona, the best Þt occurred with one-or two-locus models (Tabashnik et al 2002), and molecular work identiÞed a cadherin locus tightly linked with high levels of resistance. Diamondback moth resistance to Cry1C in the Cry1C-Sel strain from South Carolina Þt best to a one-locus model (Zhao et al 2000), and subsequent molecular mapping with a related strain (SC1) revealed contributions from two linkage groups (Baxter et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This approach follows the one described by Tabashnik et al (1992Tabashnik et al ( , 2002, except that backcrosses were done with the susceptible parental strains. The slopes of concentrationÐresponse lines for the parental strains were calculated as the mean of the slopes experimentally determined for each parental strain.…”
Section: Methodsmentioning
confidence: 99%